Hubungan perilaku Keluarga Sadar Gizi (KADARZI) dan Perilaku Hidup Bersih Sehat (PHBS) pada tatanan rumah tangga dengan status gizi balita usia 24-59 bulan - Hartono, Hartono; Widjanarko, Bagoes; EM, Mexitalia Setiawati (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: The prevalence of malnutrition among toddler in Kotabaru district was still high at 20,86 %. The family implemented Kadarzi was 56,24 % while the family who implemented PHBS was 42,48 %, this prevalence was still low. Objective: The purpose was analyzed the relationship between Kadarzi and PHBS behavior of households with nutritional status of toddler of 24-59 months. Â Methods: The design was cross sectional study conducted in Puskesmas Dirgahayu. Subjects were children aged 24-59 months who lived in Puskesmas Dirgahayu area, who coverese with inclusion and exclusion criteria twose, subjects are 90 respondens. Sampling technical by simple random sampling. Analysis tests used chi square test and logistic regression with 95% confidence level. Questionnaire was used as tools research, energy and protein intake was measured by recall method.Results: The results showed 27,8 % children was categorized as malnutrition status, 72,2 % family implemented Kadarzi and 70,0 % Kadarzi behave uncategorised healthy home. Analysis of the data showed no significant relationship between Kadarzi behavior with nutritional status (p=0,000, OR=31,13). There was a significant relationship between clean and healthy behavior with nutritional status (p=0,000, OR=22,56). Analysis of multiple logistic regression test obtained dominant factor associated with nutritional status is Kadarzi behavior (p=0,000, OR=0,08). Conclusion: There was a significant relationship between Kadarzi and PHBS behavior of households with nutritional status of toddler 24-59 months.